2008
DOI: 10.1080/01904160802325248
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Nitrate Accumulation, and Macronutrient Concentration of Pakchoi as Affected By External Nitrate-N: Amino Acid-N Ratio

Abstract: A study was carried out to determine the influence of nitrogen (N) sources on the growth, nitrate (NO − 3 ) accumulation, and macronutrient concentrations of pakchoi (Brassica chinensis L.) in hydroponics. Plants were supplied with NO − 3 and two amino acids (AA), glutamic acid (Glu), and glutamine (Gln), at six NO − 3 -N/AA-N molar ratios: (1) 100:0, (2) 80:20, (3) 60:40, (4) 40:60, (5) 20:80, (6) 0:100. The total N concentration was 12.5 mmol/L for all treatments in nutrient solutions. Both AAs reduced plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Reducing the supply of N reduces plant growth, the synthesis of enzymes, the chlorophyll content and photosynthesis 3. Through the production of active forms of cytokinins, NO 3 stimulates leaf growth and functions as an osmoticum in vacuoles, thereby causing cell extension and stimulating growth 8. In the present study, decreasing the NO 3 concentration in the NS caused reductions in the growth of the lettuce plants.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Reducing the supply of N reduces plant growth, the synthesis of enzymes, the chlorophyll content and photosynthesis 3. Through the production of active forms of cytokinins, NO 3 stimulates leaf growth and functions as an osmoticum in vacuoles, thereby causing cell extension and stimulating growth 8. In the present study, decreasing the NO 3 concentration in the NS caused reductions in the growth of the lettuce plants.…”
Section: Discussionsupporting
confidence: 45%
“…Previous studies have revealed that substituting amino acids for NO 3 can in fact stimulate growth. In pak‐choi culture, Wang et al 8 replaced 20% of the NS with 20 different amino acids and found that only the arginine treatment significantly increased the fresh and dry weights compared with the full NO 3 treatment, whereas the other amino acids decreased the fresh and dry weights in comparison with the control. Conversely, Gunes et al 9, 10 reported that replacing 20% of the NO 3 with glycine or a mixture of amino acids did not affect the fresh and dry weights of onion and winter lettuce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al (2005) (Yu et al, 2005). Studies have demonstrated that partial replacement of NO 3 -by amino acids in the nutrient solution significantly increased pakchoi quality by reducing NO 3 -content and improving vegetable nutrition (Inal and Tarakcioglu, 2001;Wang et al, 2008). These results indicated that agricultural plants could effectively use amino acid N from organic and inorganic N mixtures (eg., glycine, NH 4 + and NO 3 -).…”
Section: Discussionmentioning
confidence: 94%
“…In general, both earthworm mucus and AAs improved the accumulation of Zn, Fe, Mn and Cu (microelements) in tomato seedlings, and the effect of earthworm mucus (as a source of HA) was larger than that of AAs, although the exact trend of accumulation depended on the seedling organ (i.e., in roots, stems and leaves) (Zhang et al 2009). Wang et al (2008) compared the use of nitrate (NO 3 − ) and two AAs, glutamic acid (Glu), and glutamine (Gln), at six nitrate-nitrogen (NO 3 − -N)/amino acid-nitrogen (AA-N) molar ratios (100:0, 80:20, 60:40, 40:60, 20:80, 0:100) in nutrient solutions on the growth of 15-day-old pak choi (Brassica chinensis L.) seedlings. They found that the composition and concentrations of AA in plants changed when N source was changed to AA from ammonium (NH 4 + ) or NO 3 − , or when 80% was applied as NO 3 − -N and 20% as AA-N. Hydroponic systems generally increase yield by different ratios depending on the plant and the hydroponic system, and diminish water supply by manipulating the nutrient solution.…”
Section: Introductionmentioning
confidence: 99%